Indonesian EFL Pre-Service Teachers' Experiences in Developing Speaking Skills in the Pedagogy of Speaking Course - Ariyani, Amra; Aeni, Nur; Amaliah, Suci (LETS: Journal of Linguistics and English Teaching Studies, 2026)
This qualitative case study examines how Indonesian EFL pre-service teachers experienced the development of speaking skills in a Pedagogy of Speaking Course and how these experiences contributed to their early professional readiness. The study responds to the need for speaking pedagogy courses that support not only oral participation but also pedagogical awareness among future English teachers. Data were collected through classroom observations, semi-structured interviews with ten fourth-semester English education students, and reflective journals across four sequenced course activities: a personal speaking task, picture-based storytelling, speaking-teaching strategy mapping, and peer teaching. Using reflexive thematic analysis, data were triangulated across observations, interviews, and journal entries. The findings showed that students' speaking development progressed from personal speaking tasks to collaborative meaning-making and peer teaching. Although students encountered affective, linguistic, cognitive, and pedagogical challenges, they addressed these through self-regulation, peer collaboration, writing-based planning, digital and textual resources, and lecturer feedback. Furthermore, the course also helped students reframe and reinterpret speaking activities as vital pedagogical strategies for their future classrooms. The study concludes that a Pedagogy of Speaking Course can function as both a speaking-practice space and an early professional formation site when designed through sequenced tasks, written planning support, peer collaboration, reflective follow-up, and explicit links between speaking activities and teaching practice.